RETRACTED: COVID-19 stress and wellbeing: A phenomenological qualitative study of Pakistani Medical Doctors - Afshan, Gul; Ahmed, Farooque; Anwer, Naveed; Shahid, Sehrish; Khuhro, Mansoor Ahmed (Frontiers in Psychology, 2022)
The COVID-19 stress and increased job pressure have largely affected healthcare professionals' various life domains. This study particularly explores the effect of stress caused by treating COVID-19 patients on medical doctors' wellbeing. To explore this phenomenon, we interviewed 12 doctors treating COVID-19 patients in hospitals of metropolitan cities in Pakistan. The thematic analysis using NVivo V.12 Plus software of interviews resulted in four major themes, COVID-19 Stressors, Effects of Stress, Nature and Personality, Stress Relievers, and Stress Coping Strategies. Physicians were physically and emotionally stressed as a result of the intense work. Although they were carrying a lot of pain and hurt on their insides, participants demonstrated a sense of professional determination to overcome obstacles. Physicians are currently dealing with their emotional issues, and they should have access to complete professional help to ensure their wellbeing. The COVID-19 pandemic's mental health effects are anticipated to last far longer than the physical health effects. This study is well-positioned to investigate frontline physicians' opinions and attitudes concerning the COVID-19 and its impact on their daily lives and mental health. This research will help implement context-specific innovative mental health solutions to help the frontline workers.